2013
DOI: 10.1021/ja403807f
|View full text |Cite
|
Sign up to set email alerts
|

Metal-Cluster-Sensitized Solar Cells. A New Class of Thiolated Gold Sensitizers Delivering Efficiency Greater Than 2%

Abstract: A new class of metal-cluster sensitizers has been explored for designing high-efficiency solar cells. Thiol-protected gold clusters which exhibit molecular-like properties have been found to inject electrons into TiO2 nanostructures under visible excitation. Mesoscopic TiO2 films modified with gold clusters deliver stable photocurrent of 3.96 mA/cm(2) with power conversion efficiencies of 2.3% under AM 1.5 illumination. The overall absorption features and cell performance of metal-cluster-sensitized solar cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
360
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 300 publications
(376 citation statements)
references
References 48 publications
15
360
0
1
Order By: Relevance
“…[11][12][13][14][15][16] Applications include high-sensitivity chemical and biological sensing [17][18][19][20][21][22][23][24][25] as well as energy conversion and storage. 26,27 Anisotropic systems such as nanorods and nanowires are especially useful for certain applications such as photothermal cancer therapy. 28,29 Noble metal nanorods have two main plasmon modes: the longitudinal mode (along the main axis of the nanorod) and the transverse mode (in the plane perpendicular to the main axis).…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14][15][16] Applications include high-sensitivity chemical and biological sensing [17][18][19][20][21][22][23][24][25] as well as energy conversion and storage. 26,27 Anisotropic systems such as nanorods and nanowires are especially useful for certain applications such as photothermal cancer therapy. 28,29 Noble metal nanorods have two main plasmon modes: the longitudinal mode (along the main axis of the nanorod) and the transverse mode (in the plane perpendicular to the main axis).…”
Section: Introductionmentioning
confidence: 99%
“…To do appropriate fit the EIS measurements, the equivalent circuit shown in Figure 6 was used [29,50,53,54]. The chemical capacitance is proportional to the density of states (DOS) in the band gap, DOS increases exponentially with the proximity to the conduction band (CB), then, an increase in C µ suggest a displacement to lower energies of the TiO 2 CB.…”
Section: Electrochemical Impedancementioning
confidence: 99%
“…[3, [21][22][23][24][25][26][27][28] However, mechanistic evidence that directly supports electron transfer arising from plasmon excitation remains elusive. [3, 29,30] However, a strong increase in photoconversion efficiency with QD-sensitized Au-TiO 2 NP composite have been found which was attributed to enhanced absorption of QDs caused by increased scattering of light by the Au NPs [13,17]. Other authors, had found that Au NPs act as electron traps to help separate the photogenerated charges and subsequently improve interfacial charge transfer [10,16,[31][32][33].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, due to the significant progress in the experimental methods, it is possible to synthesize clusters with some desired properties. Among the various types of clusters, metal clusters (MC) are of much interest, firstly because of their biological and technological applications, [20][21][22][23][24][25][26][27][28][29][30] and secondly because the theoretical description of metallic systems are relatively simple.…”
Section: Introductionmentioning
confidence: 99%